Scleraxis and fibrosis in the pressure-overloaded heart. (6th October 2022) - Nagalingam, Raghu S; Chattopadhyaya, Sikta; Al-Hattab, Danah S; Cheung, David Y C; Schwartz, Leah Y; Jana, Sayantan; Aroutiounova, Nina; Ledingham, D Allison; Moffatt, Teri L; Landry, Natalie M; Bagchi, Rushita A; Dixon, Ian M C; et al.
Abstract: Aims: In response to pro-fibrotic signals, scleraxis regulates cardiac fibroblast activation in vitro via transcriptional control of key fibrosis genes such as collagen and fibronectin; however, its role in vivo is unknown. The present study assessed the impact of scleraxis loss on fibroblast activation, cardiac fibrosis, and dysfunction in pressure overload-induced heart failure. Methods and results: Scleraxis expression was upregulated in the hearts of non-ischemic dilated cardiomyopathy patients, and in mice subjected to pressure overload by transverse aortic constriction (TAC). Tamoxifen-inducible fibroblast-specific scleraxis knockout (Scx-fKO) completely attenuated cardiac fibrosis, and significantly improved cardiac systolic function and ventricular remodelling, following TAC compared to Scx +/+ TAC mice, concomitant with attenuation of fibroblast activation. Scleraxis deletion, after the establishment of cardiac fibrosis, attenuated the further functional decline observed in Scx +/+ mice, with a reduction in cardiac myofibroblasts. Notably, scleraxis knockout reduced pressure overload-induced mortality from 33% to zero, without affecting the degree of cardiac hypertrophy. Scleraxis directly regulated transcription of the myofibroblast marker periostin, and cardiac fibroblasts lacking scleraxis failed to upregulate periostin synthesis and secretion in response to pro-fibrotic transforming growth factor β. Conclusion: Scleraxis governs fibroblast activation in pressure overload-induced heart failure, and scleraxis knockout attenuated fibrosis and improved cardiac function and survival. These findings identify scleraxis as a viable target for the development of novel anti-fibrotic treatments. Structured Graphical Abstract: Structured Graphical Abstract Scleraxis was required for pressure overload-induced (via transverse aortic constriction, TAC) recruitment of RNA polymerase II to pro-fibrotic genes, activation of cardiac fibroblasts to myofibroblasts, and cardiac fibrosis. Scleraxis gene deletion attenuated fibroblast activation and fibrosis to ameliorate cardiac functional loss regardless of whether deletion occurred prior to or following TAC.